Advanced ENT MCQs : Training to pass the FRCS (ORL-HNS) Part 1 - Kullar, Peter; Muzaffar, Jameel; Manjaly, Joseph (CRC Press, 2025)
"The Intercollegiate Specialty Fellowship exam, more commonly known simply as the 'FRCS', represents a significant milestone on the way to obtaining a Certificate of Completion of Training (CCT) or Certificate of Eligibility for Specialist Registration (CESR) and becoming a consultant surgeon in the United Kingdom"--